2020
DOI: 10.1126/sciadv.aaz7001
|View full text |Cite
|
Sign up to set email alerts
|

RasGRP1 is a causal factor in the development of l -DOPA–induced dyskinesia in Parkinson’s disease

Abstract: The therapeutic effects of l-3,4-dihydroxyphenylalanine (l-DOPA) in patients with Parkinson’s disease (PD) severely diminishes with the onset of abnormal involuntary movement, l-DOPA–induced dyskinesia (LID). However, the molecular mechanisms that promote LID remain unclear. Here, we demonstrated that RasGRP1 [(guanine nucleotide exchange factor (GEF)] controls the development of LID. l-DOPA treatment rapidly up-regulated RasGRP1 in the striatum of mouse and macaque model of PD. The lack of RasGRP1 in mice (Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…In contrast, l -DOPA-treated RasGRP1 -/- mice do not display dyskinesia [ 28 ]. Moreover, l -DOPA promotes the activation of extracellular signal-regulated kinase (ERK) and mTORC1 [ 29 ]. As RasGRP1 acts as a GEF for both Ras and Rheb (another Ras family GTPase), the authors suggested that in the presence of l -DOPA, RasGRP1 could form complexes with both GTPases.…”
Section: Small Gtpases Of the Ras Familymentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, l -DOPA-treated RasGRP1 -/- mice do not display dyskinesia [ 28 ]. Moreover, l -DOPA promotes the activation of extracellular signal-regulated kinase (ERK) and mTORC1 [ 29 ]. As RasGRP1 acts as a GEF for both Ras and Rheb (another Ras family GTPase), the authors suggested that in the presence of l -DOPA, RasGRP1 could form complexes with both GTPases.…”
Section: Small Gtpases Of the Ras Familymentioning
confidence: 99%
“…As RasGRP1 acts as a GEF for both Ras and Rheb (another Ras family GTPase), the authors suggested that in the presence of l -DOPA, RasGRP1 could form complexes with both GTPases. On one hand, it could associate with H-Ras to initiate ERK signaling; on the other hand, it could activate Rheb to signal via mTOR [ 29 ]. Hence, parallel activation of these two cascades could provoke the onset and progression of L-DOPA-induced dyskinesia [ 29 ].…”
Section: Small Gtpases Of the Ras Familymentioning
confidence: 99%
See 2 more Smart Citations
“…pGEX6p2-GST-GβL was cloned from pRK5-HA-GβL into pGEX6p2-GST and was transformed into BL21 (DE3) cells (New England Biolabs) and purified using Glutathione Sepharose beads (45000139, Fisher) as described in our previous studies [34,35,65,67].…”
Section: In Vitro Sumoylationmentioning
confidence: 99%